Conflict of Norms Between the Maori Customary Burial and the New Zealand Statutory Law - Siekiera, Joanna (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
The aim of the paper is to present conflict of norms in the New Zealand legal order on the basis of Maori customary burial (tangihanga). This conflict remains unsolved, but in fact concerns many citizens. New Zealand law is a hybrid of legal and religious customs coming from the indigenous minority of Maoris on one hand and the British common law system on the other side. It needs to be underlined that the Maori customary law (tikanga) possesses de iure a position as norms of the jus cogens character. Any ruling of courts or tribunals, any act of the parliament in Wellington or any acts of administration ought to be made in accordance with tikanga. This also applies to civil law, including burial. In recent years, there were prosecuted several civil proceedings between persons of the Maori origin. The Burial and Cremation Act 1964 was set against the wills of indigenous testators. However, very often these traditional burial habits are incompatible with the domestic law standards. Thus, this paper is an attempt to demonstrate the difficult of civil law in New Zealand. This subject, nonetheless, has been grown in importance, along with greater awareness of civil society and wider possibilities of contact (both legal and extrajudicial) with the state.